Synthesis and Characterization of Visible Light Active Fe-TiO2 using Hydrothermal Method - Ibrahim, Siti Aida; Anwar, Mohamad Khairul; Ainuddin, Ainun Rahmahwati; Hariri, Azian; M.Rus, Anika Zafiah; Kamdi, Zakiah; Yunos, Muhamad Zaini; Harun, Zawati (International Journal of Integrated Engineering, 2019)
Titanium dioxide (TiO2) is well known due to it usage and has potential in purification methods of water and air pollution. In this study, TiO2 nanoparticle doped with iron (Fe) was synthesized by hydrothermal method. Effect of aging time during hydrothermal treatment on the formation of TiO2 and the performance of photocatalytic activity under visible and ultraviolet light irradiation were investigated. The structure and properties of the sample were evaluated - by X-Ray Diffraction (XRD), Energy Dispersive X-Ray (EDX), Field Emission Scanning Electron Microscope (FE-SEM) and UV-Visible Spectroscopy (UV-Vis). XRD analysis showed the studied samples consisted of anatase phase. FE-SEM images showed an agglomeration of grains with various sizes ranged 30-35 nm. Increasing aging time resulted in a narrower band gap energy and higher photocatalytic activity as compared to pure TiO2. The result showed Fe-TiO2 aged for 4 h provided the highest percentage (66%) of Methyl Orange (MO) degradation under visible light irradiation. The current finding suggested that, Fe-TiO2 has high potential to degrade organic compound in water pollution